Investigation of Microstructure and Creep Properties of Sn-xSb Solder Alloys up to Peritectic Composition - Yassin, Amal Mohamed; Khalifa, Berlent; Ismail, Reda (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Particle strengthening was studied in Sn-xSb (x=0.5–3.0 wt. %). Tensile deformation behavior of Sn-2.5 wt.% Sb is investigated at temperature ranging (298 - 343K) and under different constant loads ranging (5.1 - 14.0 MPa). The microstructure characteristics of the tested alloys have been obtained using x-ray diffraction. Morphological studies using optical microscope have been investigated to obtain correlation between the microstructure and mechanical behavior of the alloys. The improved strength is attributed to the uniform distribution of the SnSb intermetallic compound (IMC) inside b-Sn matrix. Based on the obtained stress exponent (n) and activation energy (Q), it is proposed that the dominant deformation mechanism is dislocation climb over the whole temperature range used.